Psoriasis Vulgaris Complicated by Secondary Tinea Pedis Infection: A Case Report - Sylviningrum, Thianti; Anjarwati, Dwi Utami (Medical and Health Journal, 2025)
Background: The coexistence of psoriasis vulgaris and tinea pedis presents significant diagnostic challenges due to similar clinical presentations. Chronic topical corticosteroid therapy may predispose psoriatic patients to secondary fungal infections through local immunosuppression. Case report: A 34-year-old female presented with a one-year history of erythematous, scaly, thickened lesions on bilateral feet extending above ankles, knees, elbows, and inguinal areas. Initial psoriasis vulgaris diagnosis led to treatment with topical desoximetasone 0.25% twice daily and oral cetirizine once 10mg daily. While other body sites improved significantly, bilateral foot lesions showed minimal response. Skin biopsy revealed characteristic psoriatic features including parakeratosis, Munro microabscesses, and epidermal acanthosis. Lactophenol cotton blue staining demonstrated septate hyphae with conidia consistent with Trichophyton species, confirming concurrent tinea pedis. Treatment was modified to fluconazole 150 mg weekly, topical ketoconazole 2% twice daily, and temporary corticosteroid discontinuation, resulting in significant improvement of foot lesions after three weeks.Summary: This case demonstrates the importance of comprehensive diagnostic evaluation when standard psoriasis treatment fails where the differential treatment response across anatomical sites served as a crucial indicator for further investigation emphasizing systematic approaches incorporating histopathological and microbiological examinations..